MENGELOLA PERILAKU GURU YANG MENCERMINKAN KEMATANGAN MORAL, EMOSIONAL, DAN SPIRITUAL SESUAI DENGAN KODE ETIK GURU - Fenia Marliana; Irawan Irawan (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
Teachers play a central role as role models who demand mastery of knowledge as well as moral, emotional, and spiritual maturity within the framework of the philosophy of science and the professional code of ethics. This study aims to analyze the management of teacher behavior at SDN Arjasari 03 to reflect personal and professional integrity according to ethical standards. Through a descriptive qualitative approach with intensive observation methods for three weeks in November 2025, in-depth interviews, and documentation studies, real behavioral patterns were found that align with teaching ethics. Field findings show strong indicators of moral maturity, specifically evidenced by the discipline of attendance of all teachers before 06.30 WIB and the application of the principle of objectivity in student assessment. In the emotional aspect, teachers demonstrate good self-regulation skills through self-calming techniques and a persuasive approach before giving reprimands, which impacts a conducive classroom climate. Spiritual maturity is reflected through the habit of consistent prayer at the beginning of learning throughout the class as a form of transcendental responsibility. This study concludes that the implementation of the five principles of the code of ethics—integrity, role model, emotional regulation, humanism, and spirituality—has been effective and has become a crucial foundation of school culture in shaping students' character, confirming that teacher behavior is a philosophical manifestation of dignified education. ABSTRAK Guru memegang peran sentral sebagai teladan yang menuntut penguasaan pengetahuan sekaligus kematangan moral, emosional, dan spiritual dalam bingkai filsafat ilmu dan kode etik profesi. Penelitian ini bertujuan menganalisis pengelolaan perilaku guru di SDN Arjasari 03 untuk mencerminkan integritas pribadi dan profesionalitas sesuai standar etika. Melalui pendekatan kualitatif deskriptif dengan metode observasi intensif selama tiga minggu pada November 2025, wawancara mendalam, dan studi dokumentasi, ditemukan pola perilaku nyata yang selaras dengan etika keguruan. Temuan lapangan menunjukkan indikator kematangan moral yang kuat, dibuktikan secara spesifik dengan kedisiplinan kehadiran seluruh guru sebelum pukul 06.30 WIB serta penerapan prinsip objektivitas dalam penilaian siswa. Pada aspek emosional, guru menunjukkan kemampuan regulasi diri yang baik melalui teknik self-calming dan pendekatan persuasif sebelum memberikan teguran, yang berdampak pada iklim kelas yang kondusif. Kematangan spiritual terefleksi melalui pembiasaan doa awal pembelajaran yang konsisten di seluruh kelas sebagai bentuk tanggung jawab transendental. Penelitian ini menyimpulkan bahwa implementasi lima prinsip kode etik—integritas, keteladanan, regulasi emosi, humanisme, dan spiritualitas—telah berjalan efektif dan menjadi fondasi budaya sekolah yang krusial dalam membentuk karakter peserta didik, menegaskan bahwa perilaku guru adalah manifestasi filosofis dari pendidikan yang bermartabat.